2023
DOI: 10.1039/d2py01383e
|View full text |Cite
|
Sign up to set email alerts
|

Light-accelerated depolymerization catalyzed by Eosin Y

Abstract: Retrieving the starting monomer from polymers synthesized by reversible deactivation radical polymerization has recently emerged as an efficient way to increase the recyclability of such materials and potentially enable their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 54 publications
0
81
0
Order By: Relevance
“…These techniques have been routinely shown to retain end-group functionality that can be reactivated to continue polymerization or initiate depolymerization and enable closed-loop recycling. , Depolymerization allows the retrieval of starting monomers from synthesized polymers, which can increase the recyclability of materials and potentially enable their industrial implementation. While most methods rely on high temperatures (typically from 120 to 180 °C) to trigger efficient depolymerization, recent studies by the Sumerlin and Anastasaki groups have shown that light can also be used to trigger faster and more efficient thermal depolymerization of polymers prepared by RAFT polymerization. These studies have made significant progress in the development of recyclable materials and in promoting a circular life cycle.…”
Section: Future Direction Of Raft-mediated 3d Printingmentioning
confidence: 99%
“…These techniques have been routinely shown to retain end-group functionality that can be reactivated to continue polymerization or initiate depolymerization and enable closed-loop recycling. , Depolymerization allows the retrieval of starting monomers from synthesized polymers, which can increase the recyclability of materials and potentially enable their industrial implementation. While most methods rely on high temperatures (typically from 120 to 180 °C) to trigger efficient depolymerization, recent studies by the Sumerlin and Anastasaki groups have shown that light can also be used to trigger faster and more efficient thermal depolymerization of polymers prepared by RAFT polymerization. These studies have made significant progress in the development of recyclable materials and in promoting a circular life cycle.…”
Section: Future Direction Of Raft-mediated 3d Printingmentioning
confidence: 99%
“…[31][32][33] In addition, polymers obtained from RAFT polymerization have been depolymerized by our laboratory and those of Gramlich and Sumerlin. [34][35][36][37][38] Notably, these methods have been developed to recover as much as 90% of the original monomer at temperatures as low as 120 ˚C, or even at 100 ˚C in the presence of UV or blue light irradiation. [34][35][36][37][38] Despite the aforementioned outstanding results, the vast majority of current approaches operate best in specific solvents, such as dioxane, while significantly lower depolymerization conversions are reported in alternate media, thus limiting the scope of depolymerizable materials.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] Despite the aforementioned outstanding results, the vast majority of current approaches operate best in specific solvents, such as dioxane, while significantly lower depolymerization conversions are reported in alternate media, thus limiting the scope of depolymerizable materials. [35][36][37][38] In addition, very high polymer dilutions (i.e. 0.1 mM polymer concentration or 5 mM repeat unit concentration) are typically essential to favour a successful depolymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent repor t on photo-assisted depolymerization by Anastasaki exhibited the importance of organodyes as catalysts in RAFT depolymerization system. 42 Herein we report a novel approach to take advantage of the previously reported charge transfer reactions and halogen abstracting capabilities of thus formed ionic radical species. Radical formed on the polymer main chain initiates degradation in diluted reaction conditions.…”
mentioning
confidence: 99%